Before the heroes came : Antarctica in the 1890s - Baughman, T. H., 1947- (University of Nebraska Press, 1994)
Account of the activities of the first explorer known to have landed in Antarctica, Carsten E. Borchgrevink, and of the first over-wintering in 1899.